The Effects of Breastfeeding Supports with Caregiver Program on Perception of Insufficient Breast Milk Supply, and One Month Exclusive Breastfeeding Rates among Cesarean Section Mothers - Jeenlakroy, Nachaphat; Phahuwatnakorn, Wanna; Limruangrong, Piyanun (Nursing Science Journal of Thailand, 2023)
Purpose: To study the effects of breastfeeding supports with caregiver program on perception of insufficient breast milk supply, and one-month exclusive breastfeeding rates among cesarean section mothers. Design: quasi-experimental pretest and posttest design with a comparison group. Methods: The samples consisted of 103 mothers who underwent cesarean section and stayed at the postpartum unit in a tertiary hospital, Nakhon Sawan province. Fifty-two samples in an experimental group received the program combined with usual care, whereas 51 samples in a control group received only usual care. The instruments included personal information recording form, the H & H Lactation Scale, and the Infant Feeding Interview. Data were analyzed by percentage, mean, standard deviation, t-test, and chi-square. Main findings: The mean scores of perceived insufficient breast milk supply in the experimental group prior to hospital discharge and at 1-month post discharge were significantly lower than that in the control group (t = 7.27, p < .001 and t = 3.55, p = .001 respectively). Within the experimental group, the mean scores of perceived insufficient milk supply after receiving the program prior to hospital discharge and at 1-month post discharge were significantly lower than that before receiving the program (t = 5.65, p < .001 and t = 2.62, p = .01, respectively). The rate of exclusive breastfeeding at one month in the experimental group and control group were not significantly different. (p = .18). Conclusion and recommendations: Breastfeeding supports with caregiver program can help postpartum mothers with caesarean section on perceived sufficient milk supply. Therefore, nurse-midwives should apply this program to promote awareness of breast milk adequacy and exclusive breastfeeding rate.